Food Safety Practices of Home-Based Online Food Sellers During Covid-19 Pandemic in Biliran - Balondo, Marianne Shyne C.; Du, Ernald M.; Pitao, Dannah R. (Indonesian Journal of Multidisciplinary Science, 2023)
The study aims to assess the food safety practices of home-based online food sellers during the COVID-19 pandemic in the province of Biliran. The study employed a descriptive survey design, wherein the quantitative data from online sellers were collected through a structured questionnaire. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results of the study revealed that the majority of the online food sellers in the province practice proper food safety measures. Furthermore, the majority of the respondents believe that their level of knowledge regarding food safety practices is sufficient and they possess the necessary resources to implement safe food practices. The findings of the study suggest that there is a need to encourage home-based online food sellers to enhance their knowledge of food safety practices in order to ensure the safety of the food they produce.